Development of a Clonal and High-Yield Mammalian Cell Line for the Manufacturing of a Hyperactive Human DNase I with Extended Plasma Half-Life Using PASylation® Technology - Serge M. Stamm; Roland Wagner; Dietmar A. Lang; Arne Skerra; Michaela Gebauer (Pharmaceutics, 2024)
Cumulative evidence from several pre-clinical studies suggests that restoration of plasma DNase activity in a thrombo-inflammatory state may improve clinical outcomes. Following injury, hyperactivated immune cells release large amounts of granular proteins together with DNA, which often accumulate in the surrounding environment in so-called neutrophil extracellular traps (NETs). Degradation of excess NETs by systemic DNase administration offers a promising therapeutic approach to ameliorate inflammation and dissolve intravascular clots. In order to expand the therapeutic utility of human DNase I, a variant of the enzyme was developed that has both a prolonged systemic half-life and a higher catalytic activity compared to Dornase alfa (Pulmozyme®), the recombinant form of DNase I approved for inhaled therapy of cystic fibrosis. The hyperactive enzyme was “PASylated” by genetic fusion with a strongly hydrophilic and biodegradable PAS-polypeptide to increase its hydrodynamic volume and retard kidney filtration. A stable TurboCell™ CHO-K1-based cell line was generated which is suitable for the future production of PASylated DNase I according to good manufacturing practice (GMP). Furthermore, a robust bioprocess strategy was devised and an effective downstream process was developed. The final protein product is characterized by excellent purity, favorable physicochemical properties, a 14-fold higher DNA-degrading activity than Dornase alfa and a sustained pharmacokinetic profile, with a 22-fold slower clearance in rats.